Tyrosine Phosphorylation of the Guanine Nucleotide Exchange Factor GIV Promotes Activation of PI3K During Cell Migration - Lin, Changsheng (Sci Signal, 2011)
GIV (Gα-interacting vesicle-associated protein; also known as Girdin), enhances Akt activation downstream of multiple growth factor– and G-protein–coupled receptors to trigger cell migration and cancer invasion. Here we demonstrate that GIV is a tyrosine phosphoprotein that directly binds to and activates phosphoinositide 3-kinase (PI3K). Upon ligand stimulation of various receptors, GIV was phosphorylated at Tyr(1764) and Tyr(1798) by both receptor and non-receptor tyrosine kinases. These phosphorylation events enabled direct binding of GIV to the N- and C-terminal SH2 domains of p85α, a regulatory subunit of PI3K, stabilized receptor association with PI3K, and enhanced PI3K activity at the plasma membrane to trigger cell migration. Tyrosine phosphorylation of GIV and its association with p85α increased during metastatic progression of a breast carcinoma. These results suggest a mechanism by which multiple receptors activate PI3K through tyrosine phosphorylation of GIV, thereby making the GIVPI3K interaction a potential therapeutic target within the PI3K-Akt pathway.